THE EFFECT OF LEARNING ALGORITHMS & PROGRAMMING COURSE ON THE SELECTION OF SPECIALIZATION AREA IN SOFTWARE ENGINEERING - Basrul; Arisandi, Dede (Journal of Information Technology (JINTECH), 2024)
Specialization in courses is a process of choosing part of the major or specification of the major. Specialization helps students select programs or activities according to enormous wishes based on talents, interests, and abilities. This department has three fields of interest: Software Engineering, Network Computer Engineering, and Multimedia. The condition in selecting areas of interest is that you must pass from the conditional subjects. In the RPL field request, the requirement is to give a score for the Algorithm and programming course. This study aims to determine whether Algorithms and programming Courses influence the Selection of RPL (Software Engineering) Areas of Interest in PTI. This research uses descriptive quantitative methods. This study's sample was students taking the Algorithm and Programming course, with as many as 20 respondents. This study's data collection technique is distributing questionnaires before and after students take Algorithms and Programming. The data analysis technique used is a validation test using SPSS. The result of this study is that there is an influence between Algorithm Learning and Programming on the selection of Software Engineering interests. It is marked by some students who initially did not choose the RPL field of interest to choose the RPL field of interest and vice versa. It is also reinforced by the results of the hypothesis test where the results show a significant value of < ttabel or 2,438 > 1,725 of these results can be seen in the formula If the calculation of the > ttabel at a significance level of 0.05 with df = 20, then ha is accepted, and ha is the Influence of Courses on the Selection of Areas of Interest RPL Information Technology Education Uin Ar-Raniry.